Deficiência e educação de jovens e adultos: ingresso e progressão de alunos do CIEJA-Campo Limpo, da Rede Municipal de Ensino de São Paulo - Santos, Kelly Almeida (2021)
This research, focusing on the entry and progression of students with disabilities in Youth and Adult Education – EJA -, had as aim: a) Describe and analyze the group composition of these students by type of disability or TGD, age, color/race and gender; and b) Describe and analyze the procedures used for directing students who have disabilities into study groups, as well as the progression they experience from the time they join the group until the year of data collection. For the fulfillment of these objectives, a field research was conducted based on student identification documents and pedagogical reports issued by the Integrated Center for Youth and Adult Education - CIEJA - Campo Limpo, of the São Paulo Municipal Education Network, which received statistical processing for their organization in tables that made it possible to analyze the characterization of these students, as well as the processes of initial referral to the groupings that compose the curricular structure and their school evolution. The most important findings were: a) with regard to characterization: the number of male students with disabilities was significantly larger than that of female students, more than 50% were of African ancestry, and the majority were young people with a concentration ranging from 15 to 39 years old; and b) with respect to the level of schooling: the initial pedagogical evaluation evidenced a mismatch between the level of learning presented and the final grade registered in their school documents; the vast majority of students were directed to the groupings according to the pedagogical evaluation, which evidenced incompatibility with the official records of the previous school experience and, finally, there were relatively low rates of school improvement within CIEJA itself